Laminaria Japonica polysaccharide promotes the expression of insulin receptor and reduces insulin resistance in diabetes mellitus mice - Xiao-dan, Li; Chi, Ning; Li, Shuai; Yu-xuan, Guo; De-Lin, Duan; Yun-liang, Guo (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
The aim of experiment was to investigate the effect of Laminaria Japonica polysaccharide (LJPS) on the expression of insulin receptor (InsR) and its hypoglycemic activity in type 2 diabetes mellitus mice. Type 2 diabetes mellitus models were established by feeding high fatty forage and injecting alloxan in 40 healthy male mice. The LJPS was applied as additive in physiological saline to treat the mice by intragastric administraton. The levels of fasting blood glucose (FBG) were detected by automatic blood glucose device. The tissue morphology of brainstem, liver and pancreas were stained by Hematoxylin-eosin (HE) assay and observed under light microscopy. The expression of InsR was determined by immunohistochemisty and Western blot, and the expression of InsR mRNA was detected by RT-PCR. The results indicated after treated with LJPS, the serum fasting (FBG) levels were significantly decreased than those in model group (Pï¼œ0.05). The morphology and structure of liver and pancreas tissue improved than those in model group. The expressions of InsR mRNA and protein were significantly higher than those in model group (Pï¼œ0.05). These results suggest that LJPS could play a hypoglycemic effect by promoting the expression of InsR in liver and pancreatic tissue to lessen insulin resistance (IR).